Zones of PGE–Chromite Mineralization in Relation to Crystallization of the Pados-Tundra Ultramafic Complex, Serpentinite Belt, Kola Peninsula, Russia - Andrei Y. Barkov; Andrey A. Nikiforov; Larisa P. Barkova; Vladimir N. Korolyuk; Robert F. Martin (Minerals, 2021)
The lopolithic Pados-Tundra layered complex, the largest member of the Serpentinite belt–Tulppio belt (SB–TB) megastructure in the Fennoscandian Shield, is characterized by (1) highly magnesian compositions of comagmatic dunite–harzburgite–orthopyroxenite, with primitive levels of high-field-strength elements; (2) maximum values of Mg# in olivine (Ol, 93.3) and chromian spinel (Chr, 57.0) in the Dunite block (DB), which exceed those in Ol (91.7) and Chr (42.5) in the sills at Chapesvara, and (3) the presence of major contact-style chromite–IPGE-enriched zones hosted by the DB. A single batch of primitive, Al-undepleted komatiitic magma crystallized normally as dunite close to the outer contact, then toward the center. A similar magma gave rise to Chapesvara and other suites of the SB–TB megastructure. Crystallization proceeded from the early Ol + Chr cumulates to the later Ol–Opx and Opx cumulates with accessory Chr in the Orthopyroxenite zone. The accumulation of Chr resulted from efficient cooling along boundaries of the Dunite block. The inferred front of crystallization advanced along a path traced by vectors of Ol and Chr compositions. Grains and aggregates of Chr were mainly deposited early after the massive crystallization of olivine. Chromium, Al, Zn and H 2 O, all incompatible in Ol, accumulated to produce podiform segregations or veins of chromitites. This occurred episodically along the moving front of crystallization. Crystallization occurred rapidly owing to heat loss at the contact and to a shallow level of emplacement. The Chr layers are not continuous but rather heterogeneously distributed pods or veins of Chr–Ol–clinochlore segregations. Isolated portions of melt enriched in H 2 O and ore constituents accumulated during crystallization of Ol. Levels of f O 2 in the melt and, consequently, the content of ferric iron in Chr, increased progressively, as in other intrusions of the SB–TB megastructure. The komatiitic magma vesiculated intensely, which led to a progressive loss of H 2 and buildup in f ...